Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Stuck on this proof...any help is appreciated. Here is what I have thus far.

Suppose n is odd, then n = 2j + 1 for some integers j, k, and m. then m(2j + 1) = 2jm + m. Since the product of two integers is an integer, let k= jm. => 2k + m

I'm sure I'm just not seeing some algebraic trickery here. Thx!

share|cite|improve this question
If there are no restrictions on $k$, then this assertion can fail. In particular, if $k = 2$, then $kn = 2n$ is always even. – Austin Mohr Nov 11 '12 at 4:27
Ah, good point! Thx! – electr0hed Nov 11 '12 at 4:30
up vote 1 down vote accepted

This is false, as written. If $k$ is even, then so is $kn$, regardless of whether $n$ is odd or not.

Now, suppose that $k,n$ are both odd. Then $k=2j+1$ and $n=2m+1$ for some integers $j,m$. Therefore $kn=2(\text{stuff})+1$. (I leave the determination of "stuff" to you, though I will tell you it's an integer.)

share|cite|improve this answer
Would it be fair to say, using that counterexample k = 2 would prove the assertion as it is written false then? The "fix" would be to restrict k to being odd? – electr0hed Nov 11 '12 at 4:37
Absolutely right. – Cameron Buie Nov 11 '12 at 6:27

$n=2m+1 \Rightarrow kn=2mk+k=k(2m+1)$. Note that the latter expression is the product of an integer and an odd integer, which is not always odd.

For example, Even*Odd: $(2a)\cdot (2b+1)=4ab+2a=2a(2b+1)$, which is even.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.